2001
DOI: 10.1159/000046845
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Maturation and Sensitive Periods in the Auditory Cortex

Abstract: Behavioral data indicate the existence of sensitive periods in the development of audition and language. Neurophysiological data demonstrate deficits in the cerebral cortex of auditory-deprived animals, mainly in reduced cochleotopy and deficits in corticocortical and corticothalamic loops. In addition to current spread in the cochlea, reduced cochleotopy leads to channel interactions after cochlear implantation. Deficits in corticocortical and corticothalamic loops interfere with normal processing of auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
112
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 164 publications
8
112
0
7
Order By: Relevance
“…In cases of sensory deprivation, either early-induced or congenital, the lack of environmental stimulation in one modality during the sensitive period will prevent the normal development of the system (Kral et al, 2001). On the other hand, the stronger reliance on the remaining sensory modalities also contributes to plastic reorganisation in sensory cortices.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of sensory deprivation, either early-induced or congenital, the lack of environmental stimulation in one modality during the sensitive period will prevent the normal development of the system (Kral et al, 2001). On the other hand, the stronger reliance on the remaining sensory modalities also contributes to plastic reorganisation in sensory cortices.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate a peak of reorganization in the area caudal to the primary auditory cortex, with activation from that peak spreading, in some studies, to the posterior part of the primary auditory cortex [24,37,41,48]. However, the few studies in congenitally deaf cats and deaf humans in which the primary auditory cortex was delineated on a subject by subject basis, rather than through brain averaging, indicates little functional change beyond the area caudal to the primary auditory cortex [23,49,50].It might be that adequate stimulation has not yet been used -the primary auditory cortex in the Deaf might become recruited only for visual stimuli in the far periphery or for some form of tactile stimulation -or it might be that the connectivity that would allow the primary auditory cortex to reorganize and be taken over by the remaining modalities is lacking. Indeed, research on old world primates documents inputs from other modalities one synapse away from the primary auditory cortex, but not within the primary auditory cortex proper [40,51].…”
Section: Box 2 Separating the Effects Of Deafness From Those Of The mentioning
confidence: 99%
“…In the developing visual cortex, for example, the reduction of inhibition can indefinitely extend the period during which monocular deprivation-induced alterations can occur (6). Absolute sensory deprivation has similar effects on prolonging the timing of developmental cortical plasticity, as shown by experiments involving dark-rearing and congenital deafness (7,8). We recently showed that the absence of patterned acoustic experience had similar developmental effects as no sensory input at all (9).…”
mentioning
confidence: 99%